The effect of adapted physical sport activity on people with special needs (a field study in Annaba - Bouira wilayats) - Makhlouf, Souad; Aiouadj, Sonia (sports creativity, 2025)
This study aimed to identify the effect of adapted sports physical activity on people with learning difficulties who have special needs according to the opinion of their teachers in terms of behavioral activity represented in excessive activity and the cognitive aspect represented in developing mental abilities (academic achievement) and the social aspect through the development of social communication. The two researchers used the descriptive and analytical approach on a sample of 10 special education teachers, due to the scarcity of this sample, as well as the lack of special departments for people with learning difficulties, in the states of Annaba and Bouira during the second semester of 2017, and they were chosen in an intentional way, and the study tool was an exploratory questionnaire that includes the answer On three questions according to three alternatives, we concluded that physical activity and adapted sports education affects the reduction of excessive activity, the development of mental abilities, and the development of social communication among those with learning difficulties who have special